2010
DOI: 10.1007/s10530-010-9772-1
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological responses of salt cedar (Tamarix spp. L.) to the northern tamarisk beetle (Diorhabda carinulata Desbrochers) in a controlled environment

Abstract: The northern tamarisk beetle (Diorhabda carinulata Desbrochers) was released in several western states as a biocontrol agent to suppress Tamarix spp. L. which has invaded riparian ecosystems; however, effects of beetle herbivory on Tamarix physiology are largely undocumented and may have ecosystem ramifications. Herbivory by this insect produces discoloration of leaves and premature leaf drop in these ecosystems, yet the cause of premature leaf drop and the effects of this leaf drop are still unknown. Insect h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Trees that suffer multiple years of herbivory would likely produce declining amounts of new leaves, and thus less litter through time. Results of this study and a related study in controlled greenhouse conditions (Snyder et al in press) indicated that Tamarix exposed to beetle herbivory were inefficient at conserving leaf nutrients before premature leaf drop. This idea is supported by Hudgeons et al (2007), who found that spring aboveground growth was reduced by 35% on Tamarix trees that were defoliated by beetles the previous fall in a manipulative field cage experiment in Texas and that carbohydrate concentrations were decreased in Tamarix root tissue over several years of defoliation in a field study near Lovelock, Nevada.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Trees that suffer multiple years of herbivory would likely produce declining amounts of new leaves, and thus less litter through time. Results of this study and a related study in controlled greenhouse conditions (Snyder et al in press) indicated that Tamarix exposed to beetle herbivory were inefficient at conserving leaf nutrients before premature leaf drop. This idea is supported by Hudgeons et al (2007), who found that spring aboveground growth was reduced by 35% on Tamarix trees that were defoliated by beetles the previous fall in a manipulative field cage experiment in Texas and that carbohydrate concentrations were decreased in Tamarix root tissue over several years of defoliation in a field study near Lovelock, Nevada.…”
Section: Discussionmentioning
confidence: 54%
“…Feeding by adult and larval stages of the beetle on the live leaf tissue of Tamarix causes the leaves to rapidly discolor and desiccate, and then fall from the tree during the normal summer growing season. Beetle herbivory results in damage to the leaf from scraping and chewing, as well as removal of whole sections of leaves (Snyder et al in press). The proximate cause of premature leaf drop is likely irreversible desiccation resulting from herbivore‐induced leaf wounding that reduces the plant's ability to regulate water loss (Snyder et al in press).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These feeding activities damage leaf surface structures, resulting in compromised water regulation in affected plants. Impaired water regulation results in desiccation and ultimately defoliation of the plant . Feeding by D. carinulata can dramatically increase stress on plants, potentially reducing carbon storage, impairing leaf production and reducing root mass in the years following a defoliation event .…”
Section: Introductionmentioning
confidence: 99%
“…Beetle herbivory produced greater transpiration per unit leaf area for tamarisk along the Walker River, Nevada, but these phenomena were not observed for tamarisk along the Humboldt River, Nevada (Pattison, D'Antonio, Dudley, Allander, & Rice, ). Snyder et al () in a greenhouse experiment also found greater transpiration per unit leaf area, but decreased photosynthetic rates, after beetle herbivory and before premature leaf drop. Taken together, there is little evidence for photosynthetic compensation in the remaining leaves.…”
Section: Discussionmentioning
confidence: 86%